[Whitehall - The Office of the Prime Minister] - (:unkn) unknown (My University, 2010)
The back of this post card, dated 1952, states that the building in this photograph is “Governor’s Palace” which is incorrect. The building in the photograph is "Whitehall" which houses the Office of the Prime Minister, Queen’s Park Savannah (West), Port of Spain it is listed in the Organisation of American States register of monuments of the Greater Caribbean as an important Caribbean heritage and worthy of both conservation and protection. White Hall was once the largest of the five private residences on Maraval Road, opposite the Queens Park Savannah and was built, in Corsican style with Venetian influence, at the turn of the Twentieth Century by Joseph Leon Agostini a wealthy cocoa plantation owner in Trinidad. Upon Mr. Agostini’s death in 1906, his wife sold the property, due to financial trouble, to the Henderson family who named the structure "Whitehall". The building has been described as a wedding cake by J. Newel Lewis, one of the nation’s renowned architects. In the foreground are the iron posts, railing and gate of the Queens Park Savannah and in the background is a large Samaan tree.
Colour: Black and White; Style: Landscape; Other: Bordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Historic buildings; Public buildings; Trees; Monuments; 1952; Whitehall